2011
DOI: 10.2535/ofaj.88.127
|View full text |Cite
|
Sign up to set email alerts
|

Morphology of the lingual papillae in the roan antelope

Abstract: Summary:We examined the dorsal lingual surfaces of an adult roan antelope (Hippotragus equinus) by scanning electron microscopy. Filiform, fungiform and vallate papillae were observed. The filiform papillae consisted of a larger main papilla and smaller secondary papillae. A top of the connective tissue core of the filiform papilla showed several depressions. The connective tissue core of the papilla with a long process was rarely observed. The fungiform papillae were round in shape. The connective tissue core… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

12
33
3
2

Year Published

2013
2013
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 24 publications
(50 citation statements)
references
References 13 publications
12
33
3
2
Order By: Relevance
“…The filiform papillae had oval tips. Unlike our results, these papillae have one sharp pointed tip in the cow (Chamorro et al) and Jamunapari goat (Emura et al, 2011). Secondary papillae of filiform papillae were reported in the Jamunapari goat (Emura et al, 2011) and other articles (Sonntag 1925;Agungpiriyono et al, 1995).…”
Section: Discussioncontrasting
confidence: 74%
See 3 more Smart Citations
“…The filiform papillae had oval tips. Unlike our results, these papillae have one sharp pointed tip in the cow (Chamorro et al) and Jamunapari goat (Emura et al, 2011). Secondary papillae of filiform papillae were reported in the Jamunapari goat (Emura et al, 2011) and other articles (Sonntag 1925;Agungpiriyono et al, 1995).…”
Section: Discussioncontrasting
confidence: 74%
“…Unlike our results, these papillae have one sharp pointed tip in the cow (Chamorro et al) and Jamunapari goat (Emura et al, 2011). Secondary papillae of filiform papillae were reported in the Jamunapari goat (Emura et al, 2011) and other articles (Sonntag 1925;Agungpiriyono et al, 1995). One of the important results of the study was that secondary papillae of filiform papillae were not found and this was different from other studies (Agungpiriyono et al; Dyce et al, 2004;Emura et al, 2011).…”
Section: Discussioncontrasting
confidence: 74%
See 2 more Smart Citations
“…The types of lingual papillae and their distribution have been widely investigated by scanning electron microscopy in various species, including the horse [4], chital deer [6], cattle [7][8][9], serow [10,11], buffalo [12], Saanen goat [13], camel [14], roan antelope [15], and donkey [16].…”
mentioning
confidence: 99%